2019
DOI: 10.4103/aja.aja_66_18
|View full text |Cite
|
Sign up to set email alerts
|

Does prostate-specific antigen (PSA) mass or free PSA mass improve the accuracy of predicting total prostate volume in relation to obesity in men with biopsy-proven benign prostatic hyperplasia?

Abstract: We evaluated whether the prostate-specific antigen (PSA) mass or free PSA (fPSA) mass (i.e., absolute amount of total circulating PSA or fPSA protein, respectively), versus serum PSA or fPSA concentration, improves the accuracy of predicting the total prostate volume (TPV) in relation to obesity. Among men whose multicore (≥12) transrectal prostate biopsy was negative, 586 who had a PSA of ≤10 ng ml and underwent the fPSA test prior to biopsy were enrolled. The PSA mass or fPSA mass (μ g) was calculated by mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…However, in our study, we found that the improvement in TPV prediction using PSA mass compared to serum PSA was minimal. These results are consistent with previous studies reporting only modest improvements in TPV prediction with the use of PSA mass [21]. It is possible that the effect of PSA mass on TPV estimation may differ between regions, and further studies are needed to explore this potential variability.…”
Section: Discussionsupporting
confidence: 91%
“…However, in our study, we found that the improvement in TPV prediction using PSA mass compared to serum PSA was minimal. These results are consistent with previous studies reporting only modest improvements in TPV prediction with the use of PSA mass [21]. It is possible that the effect of PSA mass on TPV estimation may differ between regions, and further studies are needed to explore this potential variability.…”
Section: Discussionsupporting
confidence: 91%